Impact of water scarcity on rural livelihood in the drought-prone region: A review of global perspectives - Jahura, Sultana; Islam, Md. Shajedul; Mostafa, M. G. (Universitas Airlangga, 2024)
Water scarcity is a challenging task for the vast majority of people in the world, which has occurred due to changes in weather patterns due to less rainfall than usual. According to perceptions, in some parts of the world, water scarcity will be more frequent and intense now. Over 200 published articles and reports from the period 2003–2023 were considered for the measurement of the global impact of water shortages on livelihoods in arid areas. Such a type of review study is designed for a systematic approach. The manuscript illustrated different dimensions of water scarcity impacts by using electronic search engines, including Google, Scopus, Science Direct, Google Scholar, PubMed, ResearchGate, and Web of Science. The study was then distinguished by including the word water scarcity with keywords such as landscape, vulnerability, adjustment, displaced person, health effect, and risk management to inquire about the necessary articles. The study results illustrated that the shortage of water during the drought period increased the misery of affected people. Droughts affect the livelihood of these people in agronomic activities, food production and security, and natural assets, causing prolonged suffering.